ssessing Situational Awareness of Universities Concerning Student Dropout: A Web-Based Content Analysis of Romanian Universities' Agenda - Adrian Hatos; Răzvan T. Coloja; Alina Sava (University Babes-Bolyai, 2020)
Universities have a strong internet presence where they publish large amounts of documents available for analysis. The relevance of these documents has been rarely put to scrutiny in a policy anlysis context. In our paper we use data from Romanian universities to achieve two objectives: 1) to assess the actual presence of the issue of student dropout at the level of universities' agenda in Romania as it is apparent in their web pages; 2) to evaluate the degree to which the agenda of Romanian universities reflects the actual issue of student retention as reflected in factual data. The results show a significant correlation between the presence of the topic in documents and the actual dropout rate, but there are some limitations, though: the correlation is not linear, universities seem to be inertial in their public aknowledgement of the problem, web-scrapping and web based content-analytic procedures still have numerous reliability issues.